Physicians’ Awareness and Drug Safety Monitoring for Adverse Drug Reactions Assessment in Bangladesh (Bangladesh Pharmaceutical Journal, 2026)
Adverse drug reactions (ADRs) remain underreported in Bangladesh despite the country's rapidly expanding pharmaceutical sector, which limits the effectiveness of national pharmacovigilance activities. Through the identification and reporting of adverse drug reactions (ADRs), doctors play a crucial role in pharmacovigilance. However, pharmacists and other medical professionals also contribute to drug safety monitoring and the degree of awareness and participation among these professionals varies significantly, especially between urban and rural settings. This study aims to measure the awareness, attitude and practice of ADR reporting among physicians in Bangladesh, explore barriers to underreporting and investigate physicians' preferences toward a mobile system for reporting ADRs. The study also examined the physicians' opinions on fundamental ADR assessment methods, which are used to format digital reporting. A cross-sectional study was conducted across the country, among a total of 200 randomly selected physicians from all eight divisions of Bangladesh (April 2022 to March 2023). Knowledge of ADR causality, severity and preventability was assessed by a structured questionnaire (Liverpool Causality Assessment Tool, Hartwig’s Severity Assessment Scale and modified Schumock-Thornton preventability scale). Findings were summarized using descriptive statistics. ADR reporting awareness was considerably higher among urban physicians (71%) compared with rural practitioners. Only 28.5% of respondents had received formal training in ADR reporting. The most common barriers included heavy workload (27.58%) and insufficient clinical expertise (24.83%). Nearly half (45.5%) preferred a mobile application due to accessibility and time efficiency. Physicians also identified specific items from the Liverpool, Hartwig and Schumock-Thornton scales that should be incorporated into a user-friendly reporting app. Significant gaps persist in physicians’ knowledge and reporting of ADRs in Bangladesh, particularly in rural areas. Strong support for mobile app-based reporting indicates a feasible strategy to enhance pharmacovigilance. Integrating digital tools with targeted training could substantially improve ADR reporting and medication safety nationwide.Bangladesh Pharmaceutical Journal 29(1): 144-153, 2026 (January)